Towards CO2 emissions reduction of shipping: Ca(OH)2 based carbon capture system for safeguarding the marine environment - Valentina Bortuzzo; Valentina Bortuzzo; Serena Bertagna; Luca Braidotti; Vittorio Bucci (Frontiers in Marine Science)
Climate change poses a global challenge related to the reduction of pollutant atmospheric emissions and the maritime transportation sector is directly involved, due to its significant impact on the production of Greenhouse Gases and other substances. While established technologies have effectively targeted emissions like Nitrogen Oxides (NOX) and Sulfur Oxides (SOX), the persistence of Carbon dioxide (CO2) emissions represents an ongoing and significant concern. Novel technologies targeting CO2 reduction have been lately studied and proposed for inland applications, and are now being developed for maritime applications. With this regard, the present study explores the potential of Carbon Capture Systems (CCS) to mitigate CO2 emissions produced by cargo ships. While the implementation of CCS faces challenges, including space limitations and logistical complexities, its possible integration onboard marks a significant step in the fight against climate change. The authors propose an innovative approach using a Calcium Hydroxide Ca(OH)2 based CCS, offering the dual benefit of CO2 reduction and the potential resolution of ocean acidification through Calcium carbonate (CaCO3), the final product resulting from the CO2 capture process. Additionally, the study examines the feasibility of the generated product for reuse in industry, promoting a circular economy and addressing environmental issues. This innovative solution underscores the urgent need for transformative measures to reduce maritime emissions, in line with efforts to safeguarding the marine environment and combat climate change.